Design of the Prevention of Adult Caries Study (PACS): A randomized clinical trial assessing the effect of a chlorhexidine dental coating for the prevention of adult caries. - Vollmer, William M.; Papas, Athena S.; Bader, James D.; Maupomé, Gerardo.; Gullion, Christina M.; Hollis, Jack F.; Snyder, John J.; Fellows, Jeffrey L.; Laws, Reesa L.; White, B Alexander. (2016)
Background: Dental caries is one of the primary causes of tooth loss among adults. It is estimated to affect a majority of Americans aged 55 and older, with a disproportionately higher burden in disadvantaged populations. Although a number of treatments are currently in use for caries prevention in adults, evidence for their efficacy and effectiveness is limited.; Springer Open.